2010
DOI: 10.1111/j.1834-7819.2010.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

The extent and nature of dental fear and phobia in Australia

Abstract: Background: For the general dental practitioner, fearful patients are harder and more stressful to treat and are most likely to attend irregularly. This study presents updated and refined dental fear and phobia prevalence estimates in Australia as well as information on the nature of dental fear and phobia. Methods: A total of 1084 Australian adults (response rate = 71.7%) completed a mailed questionnaire. The survey contained four measures of dental fear and phobia, as well as questions regarding potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 29 publications
3
93
0
12
Order By: Relevance
“…High dental fear affects approximately one in six Australian adults 1,2 and this prevalence figure is similar to that of many Western countries around the world. [3][4][5][6][7] Among some sub-groups of the population, such as middle-aged women, the prevalence of high dental fear may be as high as one in three individuals.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…High dental fear affects approximately one in six Australian adults 1,2 and this prevalence figure is similar to that of many Western countries around the world. [3][4][5][6][7] Among some sub-groups of the population, such as middle-aged women, the prevalence of high dental fear may be as high as one in three individuals.…”
Section: Introductionmentioning
confidence: 66%
“…22 Second, while it appears that dentally fearful people do report increased fear of pain, 23 the extent of this varies from person to person and there are numerous additional fear-evoking aspects of a dental visit unrelated to pain. 2,24 There are also more general issues, such as lack of control and the unpredictability of the dental experience, which may be central to the aetiology of a person's dental fear, and these are discussed in more detail below.…”
Section: Fear Anxiety Phobia and Painmentioning
confidence: 99%
“…22,24,27,28,29 In this study, most mothers were highly educated, and there was no reported history of phobic tendencies with dental treatment, so we cannot make any claims regarding a relationship between a child's dental anxiety level and their family's sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 84%
“…27,30 Next, the above analyses were performed on specific participant subgroups, based on gender, age, socioeconomic level, and previous unpleasant dental experiences, which are supported by the literature as having a significant impact on dental anxiety. The literature reports that women, 16,17,19 younger patients, 17 patients at lower socioeconomic levels, 5,19 and with previous unpleasant dental experiences 18 present greater anxiety over dental treatment. These findings may reflect a pattern of response that is distinct to the items of the DAS.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The MDAS includes a question on local anesthesia, since needle fear, phobia, and anxiety is very common in the general population. [19][20][21] However, anxiety over anesthesia may be related to the use of needles in general and not directly associated with dental treatment anxiety; needle anxiety and/or phobia has been well described in the literature. 22,23,24,25 Thus, the inclusion of this item may interfere in the true assessment of dental anxiety, since procedures involving needles are not exclusive to dentistry and, while interesting, it may overestimate anxiety over dental treatment itself.…”
Section: Introductionmentioning
confidence: 99%